Disentangling the relationships between staff nurses' workplace empowerment and job satisfaction. (28th June 2016) - Dahinten, V.S.; Lee, S.E.; MacPhee, M.
Abstract : Aim: The primary aim of this study was to examine the relationships between structural empowerment, psychological empowerment and job satisfaction among staff nurses, after controlling for their leaders' use of empowering behaviours. Background: Nurses' job satisfaction is a critical factor in health‐care organisations because of its association with nurse turnover and quality of patient care. Nurses continue to report high levels of job dissatisfaction. Methods: Cross‐sectional data for 1007 Canadian staff nurses were analysed using hierarchical multiple regression. Results: Structural empowerment was the strongest independent predictor of job satisfaction, followed by leader empowering behaviours and psychological empowerment. After accounting for the effects of structural empowerment and leader empowering behaviours, the four dimensions of psychological empowerment showed only small independent effects on job satisfaction. Psychological empowerment did not mediate the effects of structural empowerment on job satisfaction. Conclusion: Nurses' job satisfaction is most influenced by their access to organisational empowerment structures. Leader empowering behaviours, structural empowerment, and psychological empowerment, operating together, enhance nurses' job satisfaction. Implications for Nursing Management: Nurse leaders should use a variety of empowerment strategies that are important to nurses' job satisfaction and potentially to the quality of patient care and nurse turnover.